Modern Methods of Combating Infectious Diseases (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article discusses the signs of infectious diseases, ways their distribution, methods of prevention and rules of conduct. Infectious diseases are classified according to etiology, clinical course of the disease, localization of the process and source of infection. Particular attention is paid to the most common infections, ways of their spread ¬and methods of prevention.